6 spices 60 dishes : Indian recipes that are simple, fresh, and big on taste - Kahate, Ruta; Badiozamani, Ghazalle (Photographer) (San Francisco, California : Chronicle Books LLC, 2023)
Using just six spices-- cayenne, coriander, cumin, tumeric, mustard seed, and asafetida-- Kahate presents sixty recipes that are easy to prepare but deliver rich, complex flavor. The dishes include a ton of nourishing veggies, raitas, grains and dals, and are fresh, healthy, and versatile enough to mix and match with your everyday cooking. Kahate even includes Instant Pot variations, and stories from her own culinary life on two continents. -- adapted from inside front cover.
My crazy culinary journey -- One new spice; a whole new book -- Versatility is my secret sauce -- 6 spices, 3 vessels -- A few more ingredients and tools -- Health-giving soups -- Bright salads and unusual raitas -- Vegetables: leaf, fruit, flower, root -- Hearty dals and beans -- Nourishing grains and more -- Uncommon mains: eggs, seafood, and meat.
Includes index.
Keywords: Cooking, Indic; Spices; Cookbooks